2018
DOI: 10.1159/000488286
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Outcomes in French Hemodialysis Patients

Abstract: Background: Pregnancy in hemodialysis (HD) women is a rare event and often associated with maternal and fetal complications. Scarcity of available data from large cohorts impedes fair medical counseling. Methods: This is a descriptive, retrospective, multi-centric study. Pregnant women on HD during the period from 1985 to 2015 in France were included. The primary outcome was a living infant discharged from hospital, while secondary outcomes included gestational age and birth weight. Results: We identified 100 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…There are a few clinical studies regarding delivery in patients on hemodialysis. A retrospective, multicentric study consisting of 100 pregnancies in patients on hemodialysis from 1985 to 2015 in France revealed a mean gestational age of 33.2 ± 3.9 weeks and a mean birth weight of 1719 ± 730 g [20]. Another retrospective cohort study consisting of 93 pregnancies in patients on hemodialysis from 2000 to 2017 in Brazil revealed a median gestational age of 35 (12-39) and a mean birth weight of 1698 ± 719 g; in addition, preeclampsia, primigravida, average midweek BUN, polyhydramnios, and residual diuresis were associated with birth weight [21].…”
Section: Discussionmentioning
confidence: 99%
“…There are a few clinical studies regarding delivery in patients on hemodialysis. A retrospective, multicentric study consisting of 100 pregnancies in patients on hemodialysis from 1985 to 2015 in France revealed a mean gestational age of 33.2 ± 3.9 weeks and a mean birth weight of 1719 ± 730 g [20]. Another retrospective cohort study consisting of 93 pregnancies in patients on hemodialysis from 2000 to 2017 in Brazil revealed a median gestational age of 35 (12-39) and a mean birth weight of 1698 ± 719 g; in addition, preeclampsia, primigravida, average midweek BUN, polyhydramnios, and residual diuresis were associated with birth weight [21].…”
Section: Discussionmentioning
confidence: 99%
“…77 Quantifying and communicating pregnancy risk to women is an essential component of counseling. 20 In Figure 1, 42,[48][49][50]65,68,[78][79][80][81][82][83][84][85] we provide a contemporaneous "snapshot" of key perinatal and obstetrical outcomes for dialyzed and transplanted women, based on selected recent, larger studies of cohorts in developed countries. In Figure 2, we provide a "traffic light system" co-designed by patients from our Pregnancy Advisory Group.…”
Section: Actively Facilitate and Address Questionsmentioning
confidence: 99%
“…Mean weekly dialysis time in the third trimester was 20.5 ± 3.0 hours. 16 Patients with scleroderma on dialysis (N = 2385) had an increased risk of death (HR 1.4), a greater chance of renal recovery (HR 2.7), and a lesser chance of transplantation (HR 0.5) than did age, race, Fifty consecutive patients admitted to an ICU for acute kidney injury related to multiple myeloma who required dialysis were studied. Sixty days after initiating dialysis, 23 patients (46%) were alive without dialysis and 10 (20%) were still receiving it; 17 (32%) had died.…”
Section: Data From 77 607 Living Donor Transplants To Patients On Diamentioning
confidence: 99%
“…A retrospective review of 100 pregnancies (in 84 women) from 1985 to 2015 in France found a 78% fetal survival and high rates of preeclampsia (19%), hydramnios (42%), and low birth weight (45%). Mean weekly dialysis time in the third trimester was 20.5 ± 3.0 hours …”
mentioning
confidence: 99%